Factors affecting and estimates of repeatability for milk production and composition traits in several breeds of dairy cattle - HERMIZ, HANI N; HADAD, JOSHAN M (The Indian Journal of Animal Sciences, 2020)
Production records (323) were collected during two calving seasons of Bokane, Friesian and Simmental cows bred at three herds. Cows milked twice daily and milk samples collected at the peak of production to determine fat, protein, lactose, solid non-fat (SNF) %. Data was analyzed for diagnosing the significant effects of the available factors on the studied traits. Repeatability of total milk production (TMP), compositions and correlations among them were estimated. Overall mean of TMP, fat, protein, lactose, and SNF were 3,752.3 kg, 3.129%, 3.065%, 4.507% and 7.688%, respectively. TMP affected by breed, herd, parity and year of calving significantly. Regression of TMP on age at first calving was not significant (–19.597 kg/mo.), whereas regressions on body weight at calving (12.567 kg/kg) and on calf birth weight (157.63 kg/kg) were significant. Breed affects fat and protein significantly. Differences between herds in their fat, lactose and SNF% were significant. Effect of parity was significant on all milk composition except lactose %. Year of calving affects all milk compositions significantly (P